P1149Subcutaneous implantable cardioverter-defibrillator when Transvenous ICD is not a viable option. (18th June 2020) - Russo, V; Molini, S; De Bonis, S; Ziacchi, M; Ricciardi, G; Migliore, F; Viani, S; Lavalle, C; Pangallo, A; La Greca, C; Brambilla, R; Tordini, A; et al.
Abstract: Funding Acknowledgements: NO FUNDING OnBehalf: RHYTHM DETECT Registry Background: The class of recommendation for S-ICD implantation in patients who have inadequate vascular access is I according to AHA-ACC-HRS Guidelines and IIb according to ESC Guidelines. Data are lacking about the use of S-ICD for patients in which a transvenous ICD is not a viable option because of the inability to deploy a transvenous lead. Purpose: To describe current practice and to measure outcomes associated with S-ICD use in patients in which a transvenous ICD is not a viable option. Methods: 942 consecutive patients underwent S-ICD implantation at 22 Italian centers from 2014 to 2019. We identified 101 (11%) patients who received S-ICD because of the reported impossibility of deploying a transvenous lead. Results: 21 patients presented with inadequate vascular access but no previous device in place. One patient had a mechanical prosthesis in tricuspid position. The remaining 79 patients received the S-ICD after removal of a prior system implanted, and venous occlusion was diagnosed after lead extraction, or partially or completely failed lead removal. In 24 of these patients a functional transvenous pacing system was left in place for persisting pacing needs. Patients were 60 ± 15 years old, 85% were male, 77% had ischemic or non-ischemic dilated cardiomyopathy, ejection fraction was 36 ± 13%. At implantation, acute conversion test was performed in 64 patients and shock energy of ≤65J was successful in 62 (96.9%) patients. During a median follow-up of 18 months, 6 patients died for non-device related reasons and 1 patient underwent heart transplantation. One patient underwent device replacement for battery depletion and one patient underwent leadless pacemaker implantation. Minor complications (hematomas not requiring system revision) were reported in 2 patients. Appropriate therapies were delivered in 4 patients and 8 patients experienced inappropriate therapies (in 3 patients due to double counting during pacing); all resolved with device reprogramming. Conclusions: In current clinical practice, a minority of S-ICD patients receive the device because of inadequate vascular access. The profile of these patients is similar to that of the typical ICD population in the context of primary sudden death prevention, but many of them present with pacing indications. Acute and mid-term efficacy of S-ICD seemed high. Few complications occurred during follow-up. Particular attention must be paid to device programming for those patients with concomitant pacing systems, in order to prevent inappropriate therapies.